Pro PHP-GTK - Mattocks, Scott; SpringerLink (Online service) (Berkeley, CA : Apress, 2006)
PHP is gaining positive reputation for its system administration and client-side application development capabilities. This administration and development is accomplished using the PHP-GTK extension. You can take advantage of client-side applications by implementing language bindings for the GTK (the GIMP Toolkit) library for creating cross-platform graphical user interfaces. Pro PHP-GTK acts as both a definitive reference and a hands-on tutorial to the PHP-GTK extension. The book couples the extension's key topics with practical examples to guide you through a real-world project: developing a database-driven client-side inventory manager. You'll also learn how to integrate this feature with other emerging technologies like SOAP and RSS, and how to generate XML-based interfaces.
Introducing PHP-GTK -- Installing PHP-GTK -- Understanding PHP-GTK Basics -- Handling Events and Signals -- Getting an Application Up and Running -- Laying Out Applications -- Displaying and Collecting Simple Data -- Using Multiline Text -- Working with Trees and Lists -- Scrolling -- Adding Menus and Toolbars -- Adding Images -- Drag-and-Drop -- Using Selectors & Dialogs -- Doing Background Work -- Changing the Look and Feel -- Distributing PHP-GTK Applications.
Keywords: Computer science; Software engineering; Computer Science; Software Engineering/Programming and Operating Systems; Electronic books